Strategi Promosi dalam Bisnis oleh PT. BMW Astra Surabaya (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2022)
The strategy in the promotion of the company is basically important, because it greatly affects the level of success of the company. This study aims to determine the promotion strategy at PT. BMW Astra Surabaya. The researcher used a qualitative descriptive method, by collecting data using interviews and observations. The results showed that the promotion strategy at BMW Astra Surabaya came from internal and external sides. The internal side is depicted by the strengths and weaknesses of the company's activities related to promotion, while the external is depicted from the opportunities and threats. The promotional strategies carried out are in the form of: (1) advertising (advertising), (2) sales promotion by providing cashback, gifts, even free fuel for 1 (one) year, (3) sales promotion (personal selling), (4) public relations (public relations). Internal factors show an excess score of 2.18, while a deficiency score of 1.54. External factors showed the opportunity score reached 0.70, greater than the threat. An effective promotion strategy used by PT. BMW Astra Surabaya is personal selling, because it can interact directly with consumers. It is intended that consumers can be interested in buying at the same time remembering the product, thereby increasing sales. Great Opportunity owned by PT. BMW Astra Surabaya must be utilized as best as possible. Salesmen who are an important instrument for companies related to promotions must be given proper training. Loyalty of all employees is also needed to support the company's promotion strategy so that it can run effectively.